CEMENT STABILIZATION OF PURU SOIL - Artoyo
This thesis describes an investigation of the engineering properties of Puru Soil (Bangka Island) and considers the extent to which it can be used in road construction. The results indicate that Puru Soil does not meet Bina Marga Specification for unbound base and subbase material. Liquid Limit and Plasticity Index values exceed those specified, abrasion is excessive and strength, as indicated by Soaked CBR, is inadequate. Addition of a minimum of 8 - 10 percent cement results in a material that meets Bina Marga strength specification for cement stabilized base material. Strength criteria proposed by other authorities for cement bound base in lightly trafficked roads are met with the addition to Puru Soil of 3 - 6 percent .